Village Budgeting, Competence, and Their Impact on Organizational Performance and Community Satisfaction - Risa Amelia; Fina Maulida; Irwan Sutirman Wahdiat (Riviera Publishing, 2024)
Village governments play an important role in enhancing national development through effective budget management. Proper management of village funds can help improve organizational performance and community satisfaction. This study aims to identify the factors influencing village accountability in managing the Village Fund Budget and the competencies of Village Apparatus related to organizational performance. The research method used is qualitatif. The sampling technique used is purposive sampling, with respondents consisting of officials and the community in Beber Village. Data were obtained through a survey of 48 respondents. The results show that the accounting system affects the accountability of Village Fund Budget management, while the competence of village apparatus does not significantly affect the accountability of Village Fund Allocation management. This study implies that improving the village accounting system can enhance the accountability of village fund management, even though increasing the competence of village apparatus does not directly enhance such accountability. This indicates the need to focus on improving village accounting systems and procedures to achieve more accountable budget management.